2013
DOI: 10.1007/s12020-013-9898-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of a novel non-AT1, non-AT2 angiotensin binding site identified as neurolysin

Abstract: The discovery of a novel non-AT1, non-AT2 binding site for angiotensins in the rodent brain and testis that is unmasked by the organomercurial compound para-chloromercuribenzoic acid (PCMB) has catalyzed efforts to purify and characterize this protein. We recently reported that this protein is neurolysin and now report upon the specificity of this binding site for various neuropeptides. Competition binding assays in rat brain and testis used 125I-Sar1, Ile8 angiotensin II (Ang II) as the radioligand in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Also, the different metabolites of Ang II, which form after proteolytic degradation of the parent molecule, present biological activity. In addition, Ang II has high binding affinity to neurolysin which in turn may affect significantly the activity on RAS [5,6,7]. The action of Ang II on AT 1 R was the first to be studied in detail, while the mode of action of AT 2 R remained elusive for a long time owing to the lack of ligands that selectively target this receptor as also due to its low expression [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the different metabolites of Ang II, which form after proteolytic degradation of the parent molecule, present biological activity. In addition, Ang II has high binding affinity to neurolysin which in turn may affect significantly the activity on RAS [5,6,7]. The action of Ang II on AT 1 R was the first to be studied in detail, while the mode of action of AT 2 R remained elusive for a long time owing to the lack of ligands that selectively target this receptor as also due to its low expression [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the different metabolites of Ang II, which are formed after proteolytic degradation of the parent molecule, exert biological activities. In addition, Ang II has high binding affinity to neurolysin which in turn may affect significantly the activity on RAS [6][7][8] . The action of Ang II on AT 1 R was the first to be studied in detail, while the mode of action of AT 2 R remained elusive for a long time owing to the lack of ligands that selectively target this receptor as also due to its low expression [9][10][11][12] .…”
Section: The Angiotensin II Type 1 Receptor and Its Antagonistsmentioning
confidence: 99%
“…In order to amplify the applicability of water-soluble CAs in complex systems, Liu et al 182,183 reported the complexation of topotecan and irinotecan with psulphonatocalix [4]arene under 1:1 molar ratio, and the inclusion modes were confirmed by means of 1 H NMR, DSC, 2D NMR and UV-vis spectroscopy. And then Song et al 184 constructed the inclusion complex using p-sulphonatocalix [6]arene and vitamin B6 in acidic and alkaline media. The complex systems could release cargo through disaggregation of the inclusion complexes under certain conditions, which means they can act as an excellent candidate for drug delivery.…”
Section: Calixarenesmentioning
confidence: 99%